Study in Japan and the Motivation of Japanese Language Learners in Higher Educational Institutions in Indonesia - Fatmawati Djafri; Lufi Wahidati (IZUMI, 2020)
The number of Japanese learners in Indonesia ranks the second largest in the world after China. In addition to great interest in Japanese popular culture products, such as anime and manga, the enthusiasm of Japanese learners to study in Japan has become one of the main motivations for learning the Japanese language. The changing in educational policy implemented by the Japanese government has also offered a new possibility for study in Japan. This study aims to explain how the motivation to study in Japan was cultivated through the process of Japanese language learning in higher educational institutions in Indonesia. Researchers collected data using a set of a questionnaire distributed to Japanese language learners at designated universities and interviews with some of the respondents. This study focused on three issues: factors that motivate students to choose Japanese language study programs in university, language skills that learners want to develop in university, and their interest in studying in Japan. The result showed that interest in the Japanese language was the primary motivation for many learners to continue their study in higher educational institutions. The ability to communicate with native Japanese speakers was a significant achievement for a Japanese learner, but at the same time, it was a difficult task to achieve. Study in Japan provided an opportunity for learners to improve their Japanese language skills and to gain experience in Japan. These things were expected to increase the value of learners’ cultural capital and access to previously unobtainable resources.